The Effect of Company Size, Profitability, Liquidity, Inventory Intensity, and Sales Growth on Tax Aggressiveness of Non-Cyclical Consumer Companies - Widiana, Devina; Jusuf, A An Arief (PT FORMOSA CENDEKIA GLOBAL, 2024)
Taxes are one source of state income which used for the welfare of society. However, the public, namely taxpayers, including companies, have not contributed to tax payments and have taken tax-aggressive actions. This research aims to determine the effect of company size, profitability, liquidity, inventory intensity, and sales growth on tax aggressiveness in non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2019–2022. This research uses secondary data and selection using purposive sampling to find a research sample of 55 companies for the 2019–2022 period. The results of research using SmartPLS show that the company size variable has a positive effect on tax aggressiveness. Meanwhile, profitability, liquidity, inventory intensity, and sales growth have no effect on tax aggressiveness.